Knowledge based working : intelligent operating for the knowledge age - Ellis, Steve, 1960- (Chandos knowledge management series., 2005)
Covers the priorities and challenges facing organisations who are increasingly focused on 'knowledge work'; it is written from a human relations - rather than a technological - perspective. It uses real cases, backed up by evidence and analysis from a detailed study into strategic knowledge based working (KBW). The content of the book draws on two chief sources: the author's own expertise in KBW developed over five years of blue chip KBW consultancy, and the results of a previously unpublished five year study. The book offers clear, step-by-step guidance to executives who need to understand, deploy and implement KBW.